Analisis Penyisihan Kandungan Amonia dengan Stripper di Pabrik Ammonia - Jerry, Jerry; Zulfikar Luthfi, Muhammad; Nasyarudin Iqbal, Muhammad (SURYA TEKNIKA, 2024)
Ammonia industrial waste treatment is part of the final process in the industry. Wastewater containing high ammonia content needs to be treated using a stripping process. This study to analysis the stripping process for ammonia waste treatment in the industry to obtain appropriate operating conditions and meet the wastewater standards issued by the Minister of the Environment. Data obtained during 10 days of operation were compared with the standards and analyzed for column efficiency. The results of the analysis showed that the waste output with a concentration of 13.9 - 49 ppm, a pH range of 8.7 - 9 and most of the waste discharge had met the standards, namely a maximum of 50 ppm and pH 6-9. The best gas-liquid ratio at the stripper inlet is 0.25 V / V and pressure has no significant effect on stripper efficiency.